Trajectoires géographiques et paysagères de friches sportives en montagne - Laurent Astrade; Marie Forget; Christophe Gauchon; Camille Girault; Caroline Meynet (Projets de Paysage)
This article investigates the trajectories of landscapes in mountain areas developed for alpine skiing during the second half of the 20th century and looks at those where the activity is partially or totally abandoned today. From an observation of the current traces in the landscape complemented by documentary, cartographic and dendro-chronological analyses of three sites in the Vercors (Gresse-en-Vercors, the Arzelier pass and Saint-Nizier-du-Moucherotte), we study the dynamics of their abandonment through time and space. The infrastructures linked to the ski lifts that remain in place are often particularly significant and evocative, but they are the least prevalent remains and many other landscape markers, such as earthworks and woodlands, allow us to reconstruct the recent yet partly forgotten history of these sites developed as winter resorts. These different landscape trajectories, categorised according to their visibility, also make it possible to better understand the uses and values of these areas, which have been totally or partially abandoned by skiers and developers, but which have also been re-appropriated for other practices or projects.